If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8z-3(2z-4)=3(z-6)
We move all terms to the left:
8z-3(2z-4)-(3(z-6))=0
We multiply parentheses
8z-6z-(3(z-6))+12=0
We calculate terms in parentheses: -(3(z-6)), so:We add all the numbers together, and all the variables
3(z-6)
We multiply parentheses
3z-18
Back to the equation:
-(3z-18)
2z-(3z-18)+12=0
We get rid of parentheses
2z-3z+18+12=0
We add all the numbers together, and all the variables
-1z+30=0
We move all terms containing z to the left, all other terms to the right
-z=-30
z=-30/-1
z=+30
| 3(5x-5)+2=7x+11 | | 8(2w-3)-w=3(3w+2) | | 13+5x-2x=3 | | 1-2x+24x=2x+7x+49 | | 3x+4(x-17)=12 | | -3-10z=-17-16-8z | | 9x+4=-6+2x+24 | | 6n=–8+5n | | 5x-22=-2x-7 | | -4(3p+5)+8p=-11 | | x/2+3=-10/2 | | 3x+4(x-17)=-12 | | 9x+11+3x=47 | | 3f+20=-19+16f | | 7k-3.2k=15.2 | | 9-10z=129 | | 2x+12+2x+5=180 | | 3(5x-5)=7x+11 | | 18k-12=12k | | -6x-25=3+11 | | c(-13)-3=-33 | | 49-3x=7 | | 14a-7=7 | | m=-3(1,5) | | ((1/2×x)+4)+((3/4×x)-6)=2x-47 | | 25x-120=1000 | | -2(3x+5)=-5-7x | | 63=3x+3(2x-15) | | B^2=-9b | | -n+8+5n=16 | | 3c-30=27 | | -7k+19k+-16=8 |